A stochastic mine planning approach to determine the optimal open pit to underground mining transition depth – case study at the Geita gold mine, Tanzania. Issue 3 (3rd July 2022) - MacNeil, J.; Dimitrakopoulos, R.; Peattie, R.
ABSTRACT: Several of the world's largest open-pit mines are expected to consider making a transition to underground mining because of the opportunity to access an increased amount of reserves and extend a mine's life. A case study exploring the optimal transition depth from open pit to underground mining at AngloGold Ashanti's Geita gold mine in Tanzania is presented herein. The approach considered assesses the problem by evaluating the profits of a set of candidate transition depths, which have been identified by the mining operation as viable opportunities. An accurate valuation for each candidate's transition depth is derived by producing yearly mine plans based on uncertainty, which outline expected yearly cash flows. Compared with the conventional deterministic approach, the results of this study show a 23% net present value increase for the stochastic mine plans, as well as an improved production performance and the ability to meet mill requirements throughout the life-of-mine.